2010
DOI: 10.1371/journal.pbio.1000407
|View full text |Cite
|
Sign up to set email alerts
|

Human Mucosal Associated Invariant T Cells Detect Bacterially Infected Cells

Abstract: A first indication of the biological role of mucosal associated invariant T (MAIT) cells reveals that this discrete T cell subset is broadly reactive to bacterial infection. In particular MAIT cells recognize Mycobacterium tuberculosis-infected lung airway epithelial cells via the most evolutionarily conserved major histocompatibility molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
895
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 570 publications
(958 citation statements)
references
References 51 publications
41
895
3
1
Order By: Relevance
“…MAIT cells have been shown to detect a variety of microbes through the recognition of vitamin B metabolites presented by MR1 12, 81, 82. Furthermore, these cells were found to largely overlap with a unique subset of CD8+ T‐cells expressing CD161 at a high level, CD161++ CD8+ T‐cells 11, 15…”
Section: Subsets Of Cd8+ T‐cellsmentioning
confidence: 99%
“…MAIT cells have been shown to detect a variety of microbes through the recognition of vitamin B metabolites presented by MR1 12, 81, 82. Furthermore, these cells were found to largely overlap with a unique subset of CD8+ T‐cells expressing CD161 at a high level, CD161++ CD8+ T‐cells 11, 15…”
Section: Subsets Of Cd8+ T‐cellsmentioning
confidence: 99%
“…AECs play a role as immune sentinels after exposure to Mtb by presenting antigen to mucosal‐associated invariant T cells (MAITs) (Harriff et al ., 2014) and stimulating them to produce interferon (IFN)‐γ, tumour necrosis factor (TNF)‐α and granzyme, factors that may contribute to Mtb clearance. MAIT cells rapidly respond to infection, providing an early IFN‐γ boost to activate macrophages (Gold et al ., 2010). Crucially, AECs control the composition of ASL.…”
Section: Cells Involved In the Innate Immune Response To Tb In Humansmentioning
confidence: 99%
“…Increased MAIT cells in lung lesions of two patients with active TB, suggests that migration to the infected tissue is the cause of the decreased circulating numbers. In a separate study, ex vivo analysis also demonstrated that mycobacterium tuberculosis (Mtb)-reactive MAIT cells were enriched in the lungs of patients with active TB, and responded to Mtb-infected MR1-expressing lung epithelial cells [79].…”
Section: Antibacterial Activity Of Mait Cells In Vivo In Humansmentioning
confidence: 95%
“…In humans evidence of the close association between bacterial infection and MAIT cells was initially shown in patients suffering from pulmonary bacterial infections [76,79]. Decreased circulating numbers of MAIT cells were observed in patients suffering from tuberculosis (TB) compared to healthy controls and cancer patients.…”
Section: Antibacterial Activity Of Mait Cells In Vivo In Humansmentioning
confidence: 99%